Traumatic Experiences In "Columbus Circle" Movie Directed By George Gallo (2012): A Psychoanalytic Approach - Ismoyo, Lilik Toharudin, Dr. Phil. Dewi Candraningrum, S.Pd. M. Ed, Titis Setyabudi, S.S,M.Hum (2013)
This research is proposed to analyze traumatic experiences in a film with title Columbus Circle using Psychoanalytic Approach. There are two objectives. The first is to analyze the film in term of structural analysis and the second is to analyze the film based on Psychoanalytic Approach. The research paper belongs to the qualitative research. The object of the study is the personality of Abigail in Columbus Circle movie. There are two kinds of data sources used in this research, they are primary and secondary. The primary data is the film itself and the secondary data sources are biography of the author, books and internet. The technique of data collection in this research is summarizing, paraphrasing, and documenting the data. In analyzing the data, the writer employs descriptive qualitative analysis. The outcome of the study shows that the movie illustrates traumatic experiences of Abigail. The traumatic experience of Abigail begins when she sees directly, when Charlie tortures Lilian. She looks bewildered by walking back and forth. She is very worried about herself being in danger. Her painful experiences in the past, makes her more carefully in making decisions. Anxiety of Abigail turns to frighten when she lost people she cares about. Based on the analysis, the writer concludes that the problems of major character cause the conflict of her mental condition. It happens when there is contradiction between Id, Ego and Superego to overcome the trauma.